PEMANFAATAN MEDIA DIGITAL DALAM PELAYANAN PENDIDIKAN GEREJA DI ERA DIGITAL - Merensiana Hale (MURAI: Jurnal Papua Teologi Konstekstual, 2021)
The presence of the church in the midst of the world becomes a means of expressing God's will or presenting the Kingdom of God. In this calling, of course, the church continues to theology and dialogue in context. The context in it includes the times. The development of the times calls the church to theology and paraxis. Theological praxis with regard to church attendance in the digital era and the responsibility of educating people to encourage churches to adapt and innovate or transform digitally. This is important because in this digital era, there are still many churches that have not made use of digital media in their community education services. This paper aims to make the church carry out its congregational education tasks by utilizing digital media in the digital era. This article is written qualitatively using observative, analytical, argumentative methods and literature review related to digital-based church education services. The results of this paper emphasize that in this digital era, churches can reach more congregations with educational or coaching services based on digital media or social media.